Analysis of public investment and Civil Society Organizations, to solve the ecuadorian-colombian border problem, years 2016-2017-2018 - Villarreal Salazar, Fernando Javier; Chalá Maldonado, Emerson; Erazo Salazar, Favio; Imbacuán Calán, Byron (SATHIRI, 2020)
The investigation analyzed public investment and the actions of civil society organizations to counteract the problems that arose in the border area. (Imbacuán, 2019, p.11). In addition, economic, customs and unemployment problems were studied, the results of which reflect instability and negative consequences for the different productive and social sectors of the border area. To collect the information, semi-structured interviews were used with key informants from the institutions responsible at the local level and from the dependencies of the national institutions. Similarly, civil society actors affected by the problems described were investigated. The study shows that the actions that were carried out by the two sectors, were mostly unconnected and isolated, for this reason, it is advisable to overcome these difficulties with the collective construction of actions and the organization of responsibilities not only to Short term, but also long term. It also recognizes the low level of civil society organization and the limited public participation. Finally, it relates the results of other investigations, to argue the need to legislate in a specialized manner at the borders, given its problematic different from those of the centers of the countries, as well as improving the level of institutional strengthening of citizenship through the Civil society.